Accelerated increase and decrease in subjective age as a function of changes in loneliness and objective social indicators over a four-year period: results from the health and retirement study. (2nd July 2016) - Ayalon, Liat; Palgi, Yuval; Avidor, Sharon; Bodner, Ehud
Abstract : Objectives: The study examined the role of changes in loneliness and objective social indicators in the formation of changes in subjective age over a four-year period. Methods: The Health and Retirement Study is a US nationally representative study of older adults over 50 and their spouse of any age. We restricted the sample to individuals, 65 years of age and older ( n = 2591). An accelerated increase in subjective age was defined as an increase in subjective age over the two waves greater than five years. An accelerated decrease in subjective age was defined as a difference that was lower than three years. These were examined against a change in subjective age in the range of three to five years (i.e., change consistent with the passage of time). Results: For 23.4% of the sample, changes in subjective age were consistent with the passage of time. A total of 38.3% had an accelerated decrease in subjective age, whereas 38.3% had an accelerated increase. A decrease in loneliness over the two waves resulted in an accelerated decrease in subjective age, whereas an increase in depressive symptoms resulted in an accelerated increase in subjective age. Changes in objective social indicators, physical difficulties or medical comorbidity did not predict changes in subjective age. Conclusions: This is one of very few studies that examined changes in subjective age over time. Changes in subjective age represent an important construct that corresponding to other changes in subjective experiences.